2020
DOI: 10.1016/j.eng.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Natural Host–Environmental Media–Human: A New Potential Pathway of COVID-19 Outbreak

Abstract: Identifying the first infected case (patient zero) is key in tracing the origin of a virus; however, doing so is extremely challenging. Patient zero for coronavirus disease 2019 (COVID-19) is likely to be permanently unknown. Here, we propose a new viral transmission route by focusing on the environmental media containing viruses of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or RaTG3-related bat-borne coronavirus (Bat-CoV), which we term the “environmental quasi-host.” We reason that the envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 293 publications
0
18
0
Order By: Relevance
“…To our knowledge, this is the first report showing the presence of SARS-CoV-2 viral RNA in soils. Since wastewater and soils are environmental matrices rich in organic matters that can protect and shield viruses, SARS-CoV-2 might not be sanitized by disinfectants as evidenced by previous studies on other viruses ( Hurst et al, 1980 , Vettori et al, 2000 ), and possibly survive for a prolonged time in hospital outdoor environment, like over 12 hours in aerosols, over 7 days in wastewater ( Bivins et al, 2020 ), up to 28 days on surfaces ( Riddell et al, 2020 ) and >10 weeks in soils or groundwater ( Li et al, 2020a ). Thus, the presence of SARS-CoV-2 RNA on surface and in soils might pose long-term risks to surrounding residents.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first report showing the presence of SARS-CoV-2 viral RNA in soils. Since wastewater and soils are environmental matrices rich in organic matters that can protect and shield viruses, SARS-CoV-2 might not be sanitized by disinfectants as evidenced by previous studies on other viruses ( Hurst et al, 1980 , Vettori et al, 2000 ), and possibly survive for a prolonged time in hospital outdoor environment, like over 12 hours in aerosols, over 7 days in wastewater ( Bivins et al, 2020 ), up to 28 days on surfaces ( Riddell et al, 2020 ) and >10 weeks in soils or groundwater ( Li et al, 2020a ). Thus, the presence of SARS-CoV-2 RNA on surface and in soils might pose long-term risks to surrounding residents.…”
Section: Resultsmentioning
confidence: 99%
“…Natural hosts can release viruses to the surrounding environment through secretions, feces, urine, corpses, and so forth [ 77 ],. Viruses can survive in soil or water and on various surfaces in wild habitats for a prolonged period of time [ 78 ], causing potential infection in other species including humans via direct contact or intake. Domestic animals can also be infected by viruses through contact with environmental media polluted by wild animals carrying viruses [ 35 ], which makes it easier for viruses to break the ecological barrier and enter human societies through the excreta, fluids, or wastes of domestic animals during the life cycle of breeding, transportation, slaughter, and sale.…”
Section: Key Factors In the Ecological Barrier To Virial Transmission From Natural Hosts To Humansmentioning
confidence: 99%
“…Recently, the risks of SARS-CoV-2 spreading through fecal-oral and fecal-respiratory transmission have received great attention, but transmission and spread via sludge is far from well-illustrated (Carraturo et al, 2020;Foladori et al, 2020;Li et al, 2020b). A recent study showed that because sludge contains more virus particles and longer residence times, it is easier to detect SARS-CoV-2 in sludge than in sewage (Balboa et al, 2021).…”
Section: H I G H L I G H T Smentioning
confidence: 99%